Analysing uric acid levels to assess the effectiveness of dapagliflozin - Rajasekar, R.; Sundaram, Sivaraj Mohana; Raj, C. Poornima; Poovitha, M.; Kumar, Janardanan Subramonia (Clinical nutrition ESPEN, 2024)
Sodium-glucose cotransporter-2 inhibitors are an innovative diabetes treatment that lowers blood sugar levels without insulin. A growing body of evidence suggests that blood sugar levels are tightly correlated with uric acid levels in their blood and urine. To alleviate type 2 diabetes (T2DM) suffering, we tested dapagliflozin on serum and urinary uric acid levels of patients with T2DM and measured its efficacy in reducing uric acid levels. A study was conducted on 60 people with T2DM. Patients were treated with Dapagliflozin doses of 10 mg daily for 3 months. Three months later, we measured body weight, fasting, and postprandial blood glucose levels, Hemoglobin A1C (HbA1c), serum lipids, renal function tests, routine urine, and serum uric acid. A number of clinical parameters of T2DM patients were compared to those of healthy subjects of the same age group. A comprehensive analysis of all parameters was conducted to evaluate dapagliflozin's impact. After 90 days of dapagliflozin treatment, serum uric acid levels dropped significantly from 9.0 to 8 mg/dL in the dapagliflozin group, as well as uric acid percentage in urine changed from 16.1 to 23.6 %. After three months of treatment, HbA1C levels decreased from 9.8 % to 8.5 %. Following treatment with dapagliflozin, the patients' Homeostatic Model Assessment for Insulin Resistance decreased to 4.0. Further, multivariate correlation analysis showed a correlation of serum uric acid with glycemic profile positively. In conclusion, dapagliflozin lowers uric acid levels and increases insulin sensitivity in diabetic patients to improve their glycemic control.